Regulation of the activity of the promoter of RNA‐induced silencing, C3PO - Sahu, Shriya (Protein Sci, 2017)
RNA‐induced silencing is a process which allows cells to regulate the synthesis of specific proteins. RNA silencing is promoted by the protein C3PO (component 3 of RISC). We have previously found that phospholipase Cβ, which increases intracellular calcium levels in response to specific G protein signals, inhibits C3PO activity towards certain genes. Understanding the parameters that control C3PO activity and which genes are impacted by G protein activation would help predict which genes are more vulnerable to downregulation. Here, using a library of 10(18) oligonucleotides, we show that C3PO binds oligonucleotides with structural specificity but little sequence specificity. Alternately, C3PO hydrolyzes oligonucleotides with a rate that is sensitive to substrate stability. Importantly, we find that oligonucleotides with higher Tm values are inhibited by bound PLCβ. This finding is supported by microarray analysis in cells over‐expressing PLCβ1. Taken together, this study allows predictions of the genes whose post‐transcriptional regulation is responsive to the G protein/phospholipase Cβ/calcium signaling pathway.